Preparing Smart Voters: Political Education and Public Policy Awareness Among High School Students (Case Study in SMAN 2 Tejakula, SMAN 1 Sukasada, dan SMAN 1 Singaraja, Bali) - Sandiasa, Gede; Sudianing, Ni Ketut (Universitas Padjadjaran, 2026)
This study aimed to explore the role of political education and public policy internalization in improving the political intelligence of first-time voters at SMAN 2 Tejakula, SMAN 1 Sukasada, and SMAN 1 Singaraja, Bali. The method used in this study was a qualitative approach, within a case study paradigm. The case study in this research was conducted through interviews, FGDs, and observations to examine the role of political education in enhancing political intelligence and the public policy dimension among first-time voters at SMAN 2 Tejakula, SMAN 1 Sukasada, and SMAN 1 Singaraja. Empirical findings indicated that first-time voters were still at a moderate level of political intelligence and social policy sensitivity and were not yet able to connect this knowledge to a critical evaluation of candidates or policies. The high participation of first-time voters in elections was crucial for the advancement of democracy, making a good understanding of the political system and the electoral process essential for students. Political education is a primary instrument in addressing the low level of political experience, the lack of political interest, and the challenges of spreading false information that first-time voters frequently face.